HUBUNGAN PERGAULAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR SISWA KELAS IX SMA ADVENT UNKLAB - Christy Shaptary Putery Kawonal; Juwinner Dedy Kasingku; Andrew Christian Aseng; Boy Lumoindong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the relationship between peer relationships and students' learning motivation in Grade XI at SMA Advent UNKLAB during the 2023/2024 academic year. The objective is to determine the levels of peer interaction and student motivation, as well as to examine whether there is a significant relationship between the two. A quantitative research method was used, involving statistical data analysis to investigate the connection between the variables. The results of the study, based on the research questions, indicate that the level of peer interaction falls into the high category, the level of student learning motivation is also in the high category, and there is a significant relationship between peer interaction (variable X) and learning motivation (variable Y), with a moderate correlation (r = 0.471) and a significance value of sig. (2-tailed) = 0.000. These findings are expected to provide valuable insights for the public, educators, and policymakers on how to optimize peer relationships to enhance students' motivation to learn.